Elicitation of health state utilities associated with the mode of administration of drugs acting on the prostacyclin pathway in pulmonary arterial hypertension - Davies, Evan W (Patient Prefer Adherence, 2018)
INTRODUCTION: Pulmonary arterial hypertension (PAH) is a rare, incurable disease associated with decreased life expectancy and a marked impact on quality of life (QoL). There are three classes of drugs available for treatment: endothelin receptor antagonists (ERA), drugs acting on nitric oxide pathway (riociguat and phosphodiesterase type 5 inhibitors [PDE5i]), and drugs acting on prostacyclin pathway. The latter have widely different modes of administration – continuous intravenous infusion, continuous subcutaneous infusion, inhaled, and oral – each associated with variable treatment burden, and implications for health economic assessment. This study aimed to establish utility values associated with different modes of administration of drugs acting on the prostacyclin pathway for use in economic evaluations of PAH treatments. METHODS: A UK general public sample completed the EQ-5D-5L and valued four health states in time trade-off interviews. The health states drafted from literature and interviews with PAH experts (n=3) contained identical descriptions of PAH and ERA/PDE5i treatment, but differed in description of administration including oral (tablets), inhaled (nebulizer), continuous subcutaneous infusion, and continuous intravenous infusion. RESULTS: A total of 150 participants (63% female; mean age 37 years) completed interviews. Utilities are presented as values between 0 and 1, with 0 representing the state of being dead and 1 representing being in full health. The mean (SD) utility for oral health state was 0.85 (0.16), while all other health states were significantly lower at 0.74 (0.27) for inhaled (p=0.001), 0.59 (0.31) for subcutaneous (p<0.001) and 0.54 (0.32) for intravenous (p<0.001), indicating that there are disutilities (negative differences) associated with non-oral health states. Disutilities were −0.11 for inhaled, −0.26 for subcutaneous, and −0.31 for intravenous administration. CONCLUSION: The results demonstrate quantifiable QoL differences between modes of administration of drugs acting on the prostacyclin pathway. QoL burden should be considered for economic evaluation of drugs for PAH treatment.